Role of Zinc in childhood diarrhea management: a case of Nepal - Alam, Kadir; Poudel, Arjun; Palaian, Subish; Koirala, Bhawesh; Shankar, Pathiyil Ravi (Journal of Pharmacy Practice and Community Medicine)
Diarrhea is one of the leading causes of death among children less than five years of age around the world accounting for about two million child deaths annually. One of the recent strategies made to minimize the diarrhea associated mortality in children involves the use of oral zinc in diarrhea management. The inadequacy of dietary zinc uptake is exacerbated by the net loss of zinc during diarrhea. Zinc is enlisted in WHO essential drug list under medicine for diarrhea where it is indicated in acute diarrhea as an adjunct to oral rehydration salts. Zinc is usually well tolerated. It is necessary to explore public health applications, using zinc either as a preventive measure in children or therapeutically for diarrhea.
Keywords: Diarrhea; Dehydration; Mortality; Nepal; Zinc